PAW patrol. Dino rescue [videorecording (DVD)] - Chapman, Keith, 1958-; Kraft, Scott, 1959- (Paramount Home Entertainment, 2020)
Roar into a prehistoric land with the PAW Patrol in these six dino-mite tales, including two double-length missions! Join the pups as they roll into Dino Wilds to keep their new friends safe from an erupting volcano and a scheming dino egg thief. Then, the team gears up for a robotic dinosaur adventure!